Radiofrequency Ablation, Where It Stands in Interventional Radiology Today - Patel, Vipulkumar; Ritchie, Charles A.; Padula, Carlos; McKinney, J. Mark (Seminars in Interventional Radiology, 2019)
Radiofrequency ablation (RFA) is one of the first developed minimally invasive definitive cancer therapies. The safety and efficacy of RFA is well documented and has led to its incorporation into multiple international societal guidelines. By expanding on the body of knowledge acquired during the clinical use of RFA, alternative ablative technologies have emerged and are successfully competing for locoregional therapy market share. The adaption of newer ablative technologies is leading to a rapid decline in the utilization of RFA by interventional radiologists despite the lack of proven superiority. In their 2010 article, Hong and Georgiades stated “… RFA is likely to remain the mainstay of ablations for small tumors until sufficient experience emerges for the widespread acceptance for alternative ablative modalities.” Within a decade of this publication, has this time arrived?
Keywords: radiofrequency ablation; cancer; microwave ablation; cryoablation